2016
DOI: 10.2147/clep.s99479
|View full text |Cite
|
Sign up to set email alerts
|

Danish Gynecological Cancer Database

Abstract: Aim of databaseThe Danish Gynecological Cancer Database (DGCD) is a nationwide clinical cancer database and its aim is to monitor the treatment quality of Danish gynecological cancer patients, and to generate data for scientific purposes. DGCD also records detailed data on the diagnostic measures for gynecological cancer.Study populationDGCD was initiated January 1, 2005, and includes all patients treated at Danish hospitals for cancer of the ovaries, peritoneum, fallopian tubes, cervix, vulva, vagina, and ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 10 publications
0
58
0
Order By: Relevance
“…The Danish Gynecological Cancer Database (DGCD) 2005–12 includes almost all 4707 Danish patients with endometrial cancer diagnosed during the period January 1, 2005 to December 31, 2012 11. A validation study of the DGCD endometrial cancer patients demonstrated valid data especially if reported by pathologists 12.…”
Section: Methodsmentioning
confidence: 99%
“…The Danish Gynecological Cancer Database (DGCD) 2005–12 includes almost all 4707 Danish patients with endometrial cancer diagnosed during the period January 1, 2005 to December 31, 2012 11. A validation study of the DGCD endometrial cancer patients demonstrated valid data especially if reported by pathologists 12.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, according to the latest annual report (July 1, 2015YJune 30, 2016), 1853 gynecological cancer pathways were registered during this period, representing a national coverage of 89% in this period. 2 The DGCD Nursing holds a total of 436 variables. In the following, a selection of examples will be presented to illustrate the potential of the database: Table 1 displays the data entry in relation to registration period and cancer type.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an annual report 11 presenting a number of clinical quality indicators are developed by the DGCD steering committee in close cooperation with the national registry support center. 2 In accordance with the current legislation on data protection, real-time data are entered by the clinical nurses at each cancer center in an ongoing process. Subsequently, duration of hospitalization and postoperative complications are added from the National Patient Registry, and survival data are extracted from the Civil Registration System, which is updated on a day-to-day basis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations